+0  
 
0
138
1
avatar+3430 

#1 Help

NotSoSmart  Mar 16, 2018
 #1
avatar+89806 
+1

1.  The first term is 7.....only one answer has a first term  = 7

 

2.

 

8, 6, 4 , 2

 

The difference  in the successive term  to the previous term  is -2

And the first term is 8

So we have

 

a1  = 8 , an  = an-1 - 2     ⇒  first answer

 

 

3.  

 

-3, 1, 5 ,9

 

an   =  -3  + 4(n - 1) ⇒  first answer

 

 

 

cool cool cool

CPhill  Mar 16, 2018

42 Online Users

avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.